PERENCANAAN PERPANJANGAN LANDAS PACU BANDAR UDARA MARATUA DENGAN PESAWAT ATR 72 - SAPUTRA, SANDY (KURVA S JURNAL MAHASISWA, 2017)
Sandy Saputra,The Runway is a rectangular area used by aircraft for landing and take-off at airports, having a "hotmix" asphalt layer with identification of degrees and directions written in letters, as well as lines to indicate touch down or take offIn the Airport Runway planning that counts, namely Calculation of Forecasting (Forcasting), Determination of runway direction, Calculation of Pavement.Airport Runway Calculation Calculation uses Quantitative method to get forecasting results, Wind Rose Analysis Method for determining runway direction and CBR Method Method to get the results of calculating road pavement thickness on the planning of runway extension Maratua Airport with ATR 72 aircraft.